Video-based pelvic floor muscle therapy for patients with pelvic floor disorders: A Protocol for a prospective single-arm pilot and feasibility study - Linhares, Samantha M.; D’Aquila, Madeline L.; Schultz, Kurt S.; Mongiu, Anne K. (PLOS ONE, 2025)
The number of patients who suffer from pelvic floor disorders increases with age and can have a significant impact on quality of life. The first-line treatment for these different disorders includes pelvic floor rehabilitation. However, there are high rates of non-compliance with completing the recommended duration of treatment due to delays in appointments and time constraints. Thus, the primary goal of this study is to evaluate the feasibility and acceptability of an online eight-week video-based pelvic floor muscle therapy program. A secondary goal is determining whether the treatment can improve quality of life and symptoms. This study is a registry-based pilot single-arm prospective trial (NCT06689891: Video-Based Pelvic Floor Muscle Therapy). A single-arm design was utilized because our primary aim was to assess feasibility rather than comparative efficacy. Methodical guidance recommends a single-arm approach when outcomes focus on process measures instead of hypothesis testing. This design allows us to evaluate whether the intervention can be delivered as intended, establish feasibility before a larger trial, and maintain flexibility for modification without compromising a control group. Eligible participants will be offered the online program as an alternative to in-person pelvic floor rehabilitation. Primary timepoints include a pre-intervention in-person visit with a licensed pelvic floor therapist and the 8-week video-based pelvic floor muscle therapy program. There will be a midpoint evaluation followed by a post-intervention visit with the same pelvic floor therapist, where participants will be graded on their ability to complete the various exercises to assess efficacy. A survey assessing the online-based program’s usability will be conducted post-intervention. Patient-reported outcome measures, including quality of life and symptom changes, will be collected pre-, mid-, and post-intervention. As this is a pilot trial, the goal is to establish the acceptability and feasibility of a video-based pelvic floor muscle therapy program as an alternative to in-person treatment.